The Influence of the Inquiry-Based Model on Improving High Level Thinking Skills of Students at Al-Kawthar School, Lebanon: Pengaruh Model Inquiry terhadap Peningkatan Kemampuan Berpikir Tingkat Tinggi Siswa di Al-Kawthar school, Lebanon - Roua kanj (MULTIPLE: Journal of Global and Multidisciplinary, 2023)
This study aims to explore the influence of the Inquiry-Based Model on improving high-level thinking skills of students at Al-Kawthar School. High-level thinking skills are crucial aspects of students' development to face complex challenges in the era of globalization. The Inquiry Model is a learning approach that places students as active agents in the learning process by encouraging them to question, investigate, and gather information to understand the taught concepts. This research employs a quasi-experimental design with pre and posttests. The research sample consists of students at Al-Kawthar School selected through cluster random sampling. One class is assigned as the experimental group, which learns with inquiry-based learning using the Inquiry Model, while another class serves as the control group with conventional learning. A multiple-choice test of high-level thinking skills is used as the research instrument with a reliability coefficient of 0.89. The results of data analysis using independent samples t-test indicate that the Inquiry Model significantly influences the improvement of high-level thinking skills of students at Al-Kawthar School. This study provides significant implications for teaching at Al-Kawthar School. By adopting the Inquiry Model in the learning process, teachers can enhance teaching effectiveness and students' high-level thinking abilities. The findings of this research can also serve as a reference for curriculum development and teaching methods in other schools. However, it should be noted that this research has some limitations, including a limited sample size and other factors that may affect learning outcomes